Isolated laryngeal tuberculosis in a 10-year-old boy: A case report - Swain, Santosh Kumar; Das, Alok; Sahu, Mahesh Chandra (Pediatria Polska - Polish Journal of Paediatrics, 2018)
Tuberculosis is a major health problem in developing and underdeveloped countries of the world. Tuberculosis is a chronic granulomatous disease caused by Mycobacterium tuberculosis, and its incidence is rising due to increasing human immunodeficiency virus (HIV) infections. It usually affects lungs, but isolated laryngeal tuberculosis in a paediatric patient is a rare incidence. We are presenting a case of isolated laryngeal tuberculosis in a 10-year-old boy with clinical presentation of hoarseness of voice and dry irritating cough. The patient was treated with antitubercular treatment and recovery was successful with complete regression of the disease.